"Pédaler en toute sécurité": The Cycling Behavior Questionnaire (CBQ) in Belgium – A validation study. (July 2021) - Useche, Sergio A.; Philippot, Pierre; Ampe, Toon; Llamazares, Javier; de Geus, Bas
Highlights: Cycling behaviors are consistently showing up as reliable predictors of cycling crashes. This study presents the validation of the CBQ in Belgium, in two new languages: Dutch and French. The CBQ has shown good validity, reliability and consistency indicators. Cycling pattern-based differences were found for both risky and positive behaviors. This study endorses the value of the CBQ for assessing cycling behavior in further countries. Abstract: Introduction: During the last few years, the use of behavioral questionnaires for assessing risky behaviors of road users different from motor-vehicle drivers has grown considerably in applied research for road safety. In this regard, recent tools such as the Cycling Behavior Questionnaire (CBQ) are gaining ground, being adapted and tested in further languages, thus getting useful to address the case of countries whose language is different to the English and Spanish. Therefore, and in order to extend the use of the CBQ, this study aimed ( i ) to develop the validation of the CBQ to the French and Dutch languages, in order to cover the population of Belgian cyclists and (potentially) other countries speaking these languages, as well as ( ii ) to explore demographic and cycling-related differences in cycling behaviors. Methods: For this cross-sectional study, data was collected from a full sample of 1, 897 adult cyclists (50.9% males; 48.7% females; 0.4% others) from various regions of Belgium, with a mean age of 41.71 years. Results: The results suggest the CBQ, in its French and Dutch versions, has a strong factor composition, fair psychometrical properties and good convergent validity. Further, gender and cycling pattern-related differences were found in regard to the three dimensions measured by the scale. Conclusion: The results of this study support the value of the Cycling Behavior Questionnaire to be used for researchers studying road cyclists' behavior from the human factors perspective in French and Dutch-speaking countries.